1979
DOI: 10.3109/10826087909041910
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use in College Students: A Test of Sociodemographic and Reference Group Models of Explanation

Abstract: This study examined the importance of reference group variables in the understanding of drug use in college students. Other studies have investigated the role of peer orientation, and this study further elaborates on the issue by specifically looking into parents and peers as reference groups for the students. This study supports the importance of reference group variables in understanding the students' use of marijuana and/or hashish. In addition, it shows that the sociodemographic variables cannot predict dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
2
8
1
Order By: Relevance
“…= 7, p < 0.05). The results of this study appear to be similar to other studies which show that the demographic variables of sex, year in school and religiosity are factors in alcohol use [11,17,20,25].…”
Section: Alcoholsupporting
confidence: 90%
See 3 more Smart Citations
“…= 7, p < 0.05). The results of this study appear to be similar to other studies which show that the demographic variables of sex, year in school and religiosity are factors in alcohol use [11,17,20,25].…”
Section: Alcoholsupporting
confidence: 90%
“…= 5, p < 0.001) due to importance of religion, with 14.5% of not very religious compared to 4.7% of very religious individuals using marijuana at least once a year, and 6.9% compared to 1.9%, respectively, using marijuana on a monthly basis. Other recent studies [25] have also reported that religiosity is a predictor of drug-taking behaviours, and that very religious students are less likely to use a variety of substances than those who do not consider religion important to them.…”
Section: Sexmentioning
confidence: 84%
See 2 more Smart Citations
“…Only 2.1 percent of police trainees admitted to current usage of the marijuana while among law students this figure was 16.3 percent. The law students high usage of marijuana supports a study by Brown (1977) which also shows that a high number (49 percent) of law students had used the substance.The low level of marijuana use among police students is perhaps due to peer group influences (Murty, 1979) or the fact that they are more "law abiding" as a group. Other explanations might be their lower age and the rigors of discipline inherent in t he dormitory-based, institutional life style of the police sample.…”
mentioning
confidence: 99%